Biomarkers of Metabolism in Amyotrophic Lateral Sclerosis - Kirk, Siobhan E.; Tracey, Timothy J.; Steyn, Frederik J.; Ngo, Shyuan T. (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterised by the deterioration of motor neurones. However, this complex disease extends beyond the boundaries of the central nervous system, with metabolic alterations being observed at the systemic and cellular level. While the number of studies that assess the role and impact of metabolic perturbations in ALS is rapidly increasing, the use of metabolism biomarkers in ALS remain largely underinvestigated. In this review, we discuss current and potential metabolism biomarkers in the context of ALS. Of those for which data does exist, there is limited insight provided by individual markers, with specificity for disease, and lack of reproducibility and efficacy in informing prognosis being the largest drawbacks. However, given the array of metabolic markers available, the potential exists for a panel of metabolism biomarkers, which may complement other proposed biomarkers (including neurophysiology, imaging, as well as CSF, blood and urine markers) to overturn these limitations and give rise to new diagnostic and prognostic indicators.